Grafting of silver nanospheres and nanoplates onto plasma activated PET: Effect of nanoparticle shape on antibacterial activity. (September 2022) - Reznickova, Alena; Nguyenova, Hoang Yen; Zaruba, Kamil; Strasakova, Jana; Kolska, Zdenka; Michalcova, Alena; Prusa, Filip; Kvitek, Ondrej; Slepicka, Petr; Sajdl, Petr; Svorcik, Vaclav
Abstract: Antibacterial surfaces are a possible way to prevent bacterial infection. This study aim was to prepare antibacterial surface by grafting silver nanoparticles (Ag NPs) onto plasma activated polyethylene terephthalate (PET) surface via biphenyl-4, 4ˈ-dithiol (BPD). To take into account the shape factor, which may significantly influence Ag NPs antibacterial properties, two different shape were used, spherical (Ag0) and triangular (Ag3). Ag NPs were characterized using UV–Vis spectroscopy, transmission electron microscopy (TEM) and further by high resolution transmission electron microscopy (HRTEM). Average dimensions of NPs determined by TEM was 21.0 nm for Ag0 and (20.5 x 5.5) nm for Ag3. By HRTEM analysis was shape of Ag0 resolved as decahedron and Ag3 as triangular nanoplates. Success of BPD and Ag NPs grafting onto PET was proved by X-ray photoelectron and energy dispersive X-ray spectroscopy. Antibacterial tests versus E. coli and S. epidermidis were examined on the prepared substrates. Even though the higher amount of Ag was grafted on PET surface with Ag0, in case of S. epidermidis, sample with Ag3 had slightly better antibacterial activity. E. coli, on the other hand, was not affected significantly by the prepared substrates, probably due to low concentration of grafted Ag onto surface. Highlights: Polyethyleneterephthalate has been activated by plasma treatment. Silver nanospheres and triangular nanoplates has been grafted onto PET via BPD. The effect of shape of grafted NP on bactericidal activity has been evaluated. The higher bactedricidal effect showed nanoplates due to higher contact area. Materials could be used in medicine to prevent bacterial contamination of surfaces.